PENGARUH LATIHAN EGRANG DAN GOBAG SODOR TERHADAP KESEIMBANGAN TUBUH PADA SISWA SDN 1 SUBANG - Iyan Nurdiyan Haris (Program Studi Pendidikan Jasmani, STKIP Bina Bangsa Getsempena, 2017)
Body balance necessary for students in an attempt to defend the position of the body in a State of balance. Therefore the author thought to examine the influence of exercise and stilts gobag sodor against an increase in the balance of the body. The methods used in the research in experimental technique is a method of